Pengaruh Profitabilitas, Solvabilitas, Dan Pertumbuhan Perusahaan Terhadap Opini Audit Terkait Going Concern - Hendang Tanusdjaja; Michelle Kristian; Catherine Catherine (Jurnal Akuntansi dan Keuangan Daerah, 2023)
The purpose of this research is to obtain empirical evidence about the effects of profitability, solvency, and company growth on going concern audit opinion in basic materials companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. This research uses firm age as control variable. This research uses 47 samples and 141 data from basic materials companies selected by the purposive sampling method. Data processing techniques uses logistic regression analysis and processed using SPSS version 26. The result of this research indicate that profitability has a negative effect on going concern audit opinion, solvency has a positive effect on going concern audit opinion, and company growth has no significant effect on going concern audit opinion.